Design, synthesis, and biological evaluation of 5-((4-(pyridin-3-yl)pyrimidin-2-yl)amino)-1H-Indole-2-Carbohydrazide derivatives: the methuosis inducer 12A as a Novel and selective anticancer agent. (1st January 2021) - Wu, Jun; Hu, Hongyu; Ao, Mingtao; Cui, Zhenzhen; Zhou, Xiaoping; Qin, Jingbo; Guo, Yafei; Chen, Jingwei; Xue, Yuhua; Fang, Meijuan
Abstract: This study describes the synthesis and vacuole-inducing activity of 5-((4-(pyridin-3-yl)pyrimidin-2-yl)amino)-1 H -indole-2-carbohydrazide derivatives, including five potent derivatives 12c, 12 g, 12i, 12n, and 12A that exhibit excellent vacuole-inducing activity. Remarkably, 12A effectively induces methuosis in tested cancer cells but not human normal cells. In addition, 12A exhibits high pan-cytotoxicity against different cancer cell lines but is hardly toxic to normal cells. It is found that the 12A -induced vacuoles are derived from macropinosomes but not autophagosomes. The 12A -induced cytoplasmic vacuoles may originate from the endoplasmic reticulum (ER) and be accompanied by ER stress. The MAPK/JNK signalling pathway is involved in the 12A -induced methuotic cell death. Moreover, 12A exhibits significant inhibition of tumour growth in the MDA-MB-231 xenograft mouse model. The excellent potency and selectivity of 12A prompt us to select it as a good lead compound for further development of methuosis inducers and investigation of the molecular and cellular mechanisms underlying methuosis. Graphical Abstract: UF0001 HIGHLIGHTS: Novel methuosis-inducing anticancer agents are designed and synthesised. Vacuole inducers 12i and 12A display high anticancer activity and little-toxic to normal cells. Compound 12A is a selective methuosis inducer involving the activation of MAPK/JNK signalling pathway. Compound 12A effectively inhibits tumour growth in the MDA-MB-231 xenografted mouse model.